The question of water content in parsonsite: a model case - occurrence at the Cervene zily vein system, Jachymov (St. Joachimsthal), Czech Republic - Plasil,J.; Cejka,J.; Sejkora,J.; Skacha,P. (Journal of Geosciences, 2009)
Strongly altered gangue, containing rich crystalline aggregates of parsonsite, was recently found at the outcrop parts of the Cervene zily vein system, the Jachymov ore district, Czech Republic. Mineralogical research proved that in the crystal structure of parsonsite from Jachymov is present a higher content of molecular water than expected. This conclusion is supported by the results of thermogravimetric analysis and infrared spectroscopy. The weight loss obtained from TG curve is 3.70 wt. %, corresponding to 1.93 mols of H2O. The presence of a broad vibration band reflecting the O-H stretching vibrations of molecular water was ascertained in the infrared spectrum of studied parsonsite sample, suggesting that H2O molecules are involved in the hydrogen-bonding network in the crystal structure of studied parsonsite. Inferred hydrogen bond lengths can vary in the range 2.6-3.0 Å, which is consistent with the distance between possible position of the molecular water and nearest neighbouring oxygen atom in the crystal structure of the synthetic parsonsite given in literature. The chemical composition of the studied parsonsite from Jachymov, 47.27 PbO, 13.38 P2O5, 1.60 As2O5, 0.16 SiO2, 32.61 UO3, 3.70 H2O, total 98.71 wt. %, can be expressed as Pb1.99(UO2)1.07 [(PO4)1.77(AsO4)0.13(SiO4)0.03]Σ1.93.1.93 H2O, based on electron microprobe and thermal analyses. Its refined unit-cell parameters for triclinic space group P-1, a 6.860(2), b 10.404(3), c 6.665(3) Å, α 101.46(3)O, β 98.30(3)o, γ 86.29(2)o, V 461.0(3) Å3 agree very well with the published data.
Keywords: parsonsite; Jachymov; powder X-ray diffraction; EMPA; infrared spectroscopy; thermal analysis; O-H bonding